Does the US IT stock market dominate other IT stock markets : Evidence from multivariate GARCH model - Zhuo, Qiao; Venus, Khim-Sen Liew; Wing-Keung, Wong (Economics Bulletin, 2007)
Utilizing multivariate GARCH framework, this study finds that generally the US Information Technology (IT) market contributes a strong volatility rather than mean spillover effect to non-US IT markets, implying that the US IT market plays a dominant role in affecting the volatility of world IT markets. However, our further analysis of the dynamic path of correlation coefficients reveals that the strong relationship between US and non-US IT markets had weakened after the burst of the IT bubble.